Aplicación móvil para la gestión de venta de medicamentos en la empresa farmamovil - Bustillos Cachago, Luis Miguel (2016)
In this researching project with the theme "MOBILE APPLICATION FOR THE MANAGEMENT OF DRUG SALE IN THE COMPANY FARMAMOVIL" offers the service of selling drugs at home also giving benefits to customers in institutions sponsoring company. However, this was done through phone calls or text messages, which is a traditional way to make such orders. So this project is intended to automate the ordering of medicines needed by persons from their homes or workplaces, through the use of Android devices with internet access, benefiting the people of the city of Latacunga. This application allows the customer to place your order, by sending complete prescriptions. So there is the option to upload a photo of the prescription, same that reaches the administrator or dispatcher, billing and bringing the product to its final destination. In addition, the dealer can be guided on the place where it will be delivered the product as the application detects the location of the customer while entering your prescription, so that the use of geolocation evidence.